Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1001/jamaneurol.2021.1055
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Life-Year Costs of Treatment Speed From Arrival to Endovascular Thrombectomy in Patients With Ischemic Stroke

Abstract: The benefits of endovascular thrombectomy (EVT) are time dependent. Prior studies may have underestimated the time-benefit association because time of onset is imprecisely known.OBJECTIVE To assess the lifetime outcomes associated with speed of endovascular thrombectomy in patients with acute ischemic stroke due to large-vessel occlusion (LVO).DATA SOURCES PubMed was searched for randomized clinical trials of stent retriever thrombectomy devices vs medical therapy in patients with anterior circulation LVO with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…We add new evidence, showing that the scope of this learning curve exceeds early MT structure establishment and persists in regularly used MT environments with substantial procedural volume—all sites in our analysis performed at least 35 MTs/year with a median of 146 yearly procedures. Intra-hospital time delay, which we observed in low-volume centers have recently been shown to be particularly associated with loss of healthy life—years ( 17 ) and should be addressed by in-depth analysis and optimization of the local MT workflow. Overall time from symptom onset/time of recognition to flow restoration appeared not to be different in high- vs. low-volume centers.…”
Section: Discussionmentioning
confidence: 96%
“…We add new evidence, showing that the scope of this learning curve exceeds early MT structure establishment and persists in regularly used MT environments with substantial procedural volume—all sites in our analysis performed at least 35 MTs/year with a median of 146 yearly procedures. Intra-hospital time delay, which we observed in low-volume centers have recently been shown to be particularly associated with loss of healthy life—years ( 17 ) and should be addressed by in-depth analysis and optimization of the local MT workflow. Overall time from symptom onset/time of recognition to flow restoration appeared not to be different in high- vs. low-volume centers.…”
Section: Discussionmentioning
confidence: 96%
“…We have demonstrated that team prenotification with an EVT-call, which informs all team members about impending arrival and expected arrival time of patients who are potentially eligible for EVT, can decrease in-hospital treatment times and—potentially—improve functional outcomes of acute stroke patients. Door-to-groin puncture time reduction of 15 min translates into nearly 3 months healthy life-time gain, on average, emphasizing its clinical relevance ( 4 ). Several aspects that could further decrease treatment times (e.g., necessity for repeated imaging, periinterventional general anesthesia) and methods to effectively select patients in the preclinical or early clinical setting need to be analyzed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In patients who qualify for EVT in the neuro-interventional hospital, each 30 min increase of CT-to-reperfusion time is associated with a nearly 10% decreased chance to achieve a favorable outcome ( 3 ). Moreover, with each second of delay between arrival to groin puncture, the patient loses 2.2 h of healthy life-time ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been estimated that every 1-s delay to reperfusion results in a loss of 2.2 hours of healthy life. 1 Accordingly, treatment aimed at delaying infarct progression until definite reperfusion can be achieved by pharmacological or mechanical means is a highly promising strategy to maximize the treatment efficacy and improve patient outcomes.…”
mentioning
confidence: 99%